Past and present dynamics of sorghum and pearl millet diversity in Mount Kenya region. (23rd September 2016) - Labeyrie, Vanesse; Deu, Monique; Dussert, Yann; Rono, Bernard; Lamy, Françoise; Marangu, Charles; Kiambi, Dan; Calatayud, Caroline; Coppens d'Eeckenbrugge, Geo; Robert, Thierry; Leclerc, Christian
Abstract: Crop populations in smallholder farming systems are shaped by the interaction of biological, ecological, and social processes, occurring on different spatiotemporal scales. Understanding these dynamics is fundamental for the conservation of crop genetic resources. In this study, we investigated the processes involved in sorghum and pearl millet diversity dynamics on Mount Kenya. Surveys were conducted in ten sites distributed along two elevation transects and occupied by six ethnolinguistic groups. Varieties of both species grown in each site were inventoried and characterized using SSR markers. Genetic diversity was analyzed using both individual‐ and population‐based approaches. Surveys of seed lot sources allowed characterizing seed‐mediated gene flow. Past sorghum diffusion dynamics were explored by comparing Mount Kenya sorghum diversity with that of the African continent. The absence of structure in pearl millet genetic diversity indicated common ancestry and/or important pollen‐ and seed‐mediated gene flow. On the contrary, sorghum varietal and genetic diversity showed geographic patterns, pointing to different ancestry of varieties, limited pollen‐mediated gene flow, and geographic patterns in seed‐mediated gene flow. Social and ecological processes involved in shaping seed‐mediated gene flow are further discussed.